Storage stability of vacuum-packaged hotsmoked Rainbow trout (Oncorhynchus mykiss) fillets: organoleptic, biochemical and microbiological aspects. - ELEFTHERIADOU (Α. ΕΛΕΥΘΕΡΙΑΔΟΥ), A.; AMBROSIADIS (Ι. ΑΜΒΡΟΣΙΑΔΗΣ), I.; VARELTZIS (Κ. ΒΑΡΕΛΤΖΗΣ), K.; GEORGAKIS (ΣΠ. ΓΕΩΡΓΑΚΗΣ), S. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of this research was to investigate some problems related to Rainbow trout's (Oncorhynchus mykiss) hot-smoking process as well as the quality evaluation of the final product. The skin-on and skin-off fillets were hotsmoked and kept in vacuum-packed storage at 2°C±0,1. Organoleptic, biochemical and microbiological analyses were carried out during 120 days of storage. The taste panel assessors were asked to score the smoke intensity, the saltiness, the juiciness and the overall acceptability of the smoked samples. Generally speaking thoughout the study period of organoleptic analyses considerable changes were not observed. The total volatile nitrogen (TVN) content remained lower than 25 mg/Kg smoked fish, till the 120th day of storage. An increase of the malonaldehyde content up to 2,0 mg/Kg was noted at the 120th day of storage. At the same time the nitrite content was decreased from 34 ppm to 10 ppm. The microbiological examinations showed that the total viable count, the phsychrotrophs and lactic acid bacteria gradually exhibited a significant increase at the end of the 120th day of storage.